The keratinized mucosa width at partially edentulous molar sites and its associated factors: a pilot study - Ziyao Han; Cui Wang; Yiping Wei; Gang Yang; Wenjie Hu; Kwok-Hung Chung (BMC, 2022)
Abstract Background Assessment of the keratinized mucosa width (KMW) at edentulous sites is important for the subsequent implant treatment design. This pilot study aimed to evaluate the characteristics of the KMW at edentulous molar sites and explore the associated factors. Methods A total of 150 patients with 222 edentulous molar sites were included. The buccal KMW of the edentulous molar sites was measured during implant treatment planning. Potentially associated factors, including age, sex, smoking status, location, reasons for tooth loss/extraction, gingival phenotype (GP) and keratinized gingival width (KGW) of the adjacent teeth, were collected and analyzed. The Shapiro‒Wilk test, Student's t test, one-way ANOVA, generalized estimation equations (GEEs) and linear regression analysis were used for data analysis at α = 0.05. Results The buccal KMW at edentulous molar sites was 3.97 ± 2.06 mm, and 41.9% of sites presented with KMW < 4 mm. The mean KMWs of the maxillary sites were significantly higher than that those of the mandibular sites (4.96 ± 2.05 mm vs. 3.41 ± 1.85 mm, respectively). In total, 54.7%, 46.5%, 29.8%, and 0.0% of mandibular first and second molar sites and maxillary first and second molar sites, respectively, displayed a KMW of < 4 mm. Statistically significant linear correlations were found between KMW and GP (r = 0.161, p = 0.025) and between KMW and KGW of the adjacent teeth (r = 0.161, p = 0.023), while other factors were found to have no significant association. Conclusion Within the limitations of the present study, the KMW at edentulous molar site was related to the location of molar tooth loss/extraction. The GP and KGW of the adjacent teeth of edentulous molar sites were also associated with their KMW, which was probably attributed to the continuity of the adjacent soft tissue.